Challenges of Forensic Evidence in Cross-Border Proceedings: Standardisation and Reliability in International Cybercrime Cases - Kudeikina, Inga (Національний науковий центр «Інститут судових експертиз ім. Засл. проф. М.С. Бокаріуса», 2026)
Forensic evidence plays an essential role in cross-border proceedings, particularly in the context of international cybercrime, where its reliability and mutual recognition become increasingly important. However, differences in legal frameworks, forensic methodologies, and quality standards create challenges for the consistent evaluation and use of such evidence across jurisdictions. The aim of this article is to examine the key challenges related to the standardisation and reliability of forensic evidence in cross-border proceedings, with particular attention to international cybercrime. The study is based on the analysis of legal frameworks and legal doctrine, applying an analytical and systematic research approach.
Keywords: forensic evidence; expert evidence; cross-border proceedings; standardisation; reliability of evidence; cybercrime